The Imperium of Fate and Coincidence in Thomas Hardy (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study examines the theme of fate and coincidence in the works of Thomas Hardy, focusing on how these elements influence the lives of his characters and shape the narrative. Through a comprehensive analysis of secondary sources, the study aims to shed light on Hardy's portrayal of the imperium of fate and coincidence in his novels and poems, highlighting the philosophical and existential questions raised by these themes in his literary works.